Pengaruh Pemikiran Hazairin Terhadap Politik Hukum Pidana Islam di Indonesia - Muhamad Taufik Kustiawan (Assosiation of Islamic Education Lecturer of Universitas Jenderal Soedirman, 2021)
Abstract: Hazairin is one of the legal thinkers who paid great attention to Islamic criminal law in the twentieth century in Indonesia. The influence of Western culture has had a positive impact in redefining the developing legal sciences as a source of material law for national law. He is a progressive thinker who studies civil law, anthropology and customary law. Since colonial times, Hazairin is a legal expert who has been persistent in fighting for the application of Islamic law in Indonesia. This idea can be proven as his rejection of Snouck Hurgronje's theory. He could not accept reception's theory that developed during the colonial period because it was against Islamic law. Hazairin argued that Snouck Hurgronje's theory had the aim of diminishing the existence of Islamic law in Indonesia. So that in order to understand Hazairin's thoughts in reconstructing Islamic criminal law in Indonesia, the writer needs to examine the concept of shari'ah's critical reasoning from the theory of Muhammad Said Al-Asymawi. In this theory, it describes the principles of shari'ah, in general, to explain the arguments for the application of Islamic shari'ah to be in accordance with the source of law (the Quran and Hadis) by looking at historical and sociological reviews. This research is qualitative research using a lot of library data (library research). Therefore, this research concludes that the influence of Hazairin's thoughts on Islamic criminal law is very large in developing Islamic law as a material source of national law in Indonesia.